Atomically dispersed metal active centers as a chemically tunable platform for energy storage devices. Issue 31 (27th May 2020) - Xia, Huicong; Qu, Gan; Yin, Hengbo; Zhang, Jianan
Abstract : Atomically dispersed materials with maximized atom utilization, abundant active centers, and ultrahigh chemical reaction activity can accelerate the reaction kinetics in energy storage devices and have excellent electrochemical performance. Abstract : Electrochemical energy storage devices play an indispensable role in the exploitation of renewable, clean, and environment-friendly resources. The most preferred route is the use of energy directly. However, the efficiency of energy conversion and storage is dependent on the activity of the electrode catalyst materials. At present, most of the catalyst materials suffer from shortcomings such as low utilization and low activity, which cannot meet the ever-growing demands. Thus, it has become increasingly important to develop a catalyst with high efficiency and improve the coulombic efficiency of electrochemical energy storage devices. Because of the unique electronic and structural features, atomically dispersed (AD) metal active centers exhibit maximum utilization, high active center density, and ultra-high electrochemical activity. In particular, AD metal catalysis has shown excellent performance in electrocatalytic energy conversion and it has also become a new star in other aspects. The present review summarizes the catalytic activity and mechanism with respect to the recent progress in AD metal active centers as a chemically tunable platform for energy storage devices. Furthermore, the current challenges and perspectives of the AD metal research area are discussed. We sincerely expect that this review can provide some inspiration for the future of AD active centers in energy storage and actively promote the development of this emerging research area.